Description of a new species of Chonala (Lepidoptera, Nymphalidae, Satyrinae) from NW Yunnan, China - Lang, Song-Yun; Bozano, Gian Cristoforo (Zootaxa, 2016)
A new species, Chonala huertasae Lang & Bozano sp. nov., is described from Dulong-jiang valley, West slope of Mts. Gao-li-gong, NW Yunnan Province, SW China. A key to species and subspecies of the genus Chonala is given.